Pengaruh Kompetensi Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Empiris pada Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah (DPPKAD) Kabupaten Boyolali) - Pamungkas, Vita Putri; , Drs. Eko Sugiyanto, M.Si (2017)
The study aimed to determine the effect of human resource competency and the utilization of information technology on the Quality of local Government Financial Report (LKPD) in DPPKAD of Boyolali regency. This research uses quantitative method with primary data that collecting questionnaire. Population of this research is employee department staff at DPPKAD Boyolali. The used sampling method is the saturated samples. Data collection is done by giving as many as 84 copies of the questionnaire, which was distributed to respondents on DPPKAD of Boyolali Regency. Sum samples are 43 respondent. Analysis tool uses validity, reliability, normality, multicolinierity, heteroscedasticity, regression linier, F, t, and coefficient determination test. The data obtained are then analyzed using SPSS 21.00. Based on the analysis result, obtained that the human resource competency and the utilization of information technology has significant effect on the Quality of local Government Financial Report (LKPD) in DPPKAD of Boyolali Regency. Keyword: human resource competency, the utilization of information technology, and quality of local government financial report.